ANALISIS PERSEPSI KUALITAS PERKULIAHAN DI LABORATORIUM PERKANTORAN DAN SEKRETARI PROGRAM PENDIDIKAN VOKASI UNIVERSITAS INDONESIA - Istiadi Istiadi; Mohammad Ridha (Jurnal Vokasi Indonesia, 2016)
Laboratory of the study Program is the on factor that imfluence the quality of student in the process of theirstudy in Vocational Program . In order that, laboratory must become the crucial factor in producing qualifiedalumni.The quality of teaching ini laboratory in general was imfluenced some factors like: lecturer/instructur,curicullum, tools or su pported facilities in laboratory. For that reason, in this research we want to know thegeneral of student in laboratory teaching. Factors that was identified included : degree of studentsatisfaction, quality of teaching, and laboratory supporting facilities . Output of this research is benefited asthe input in developing the ideal office and Secretary Laboratory that sincronized with student needs.Keyword; Laboratory, quality of teaching, facility, curicullum, student satisfaction.